Legal Analysis of Judges' Considerations in Assessing The Element of Intention in The Criminal Act of Murder (Study of Decision Number 91/Pid.B/2024/PN Kln) - Fadhillah Zahwa Yusticia; Syaifuddin Zuhdi (Universitas Muhammadiyah Surakarta, 2026)
The crime of murder is a severe crime against human life, expressly regulated in Article 338 of the Indonesian Criminal Code (KUHP). In criminal justice practice, proving the element of intent and the judge's considerations often involve analysis of evidence, including the testimony of forensic experts. This study analyzes the judge's considerations in Decision Number 91/Pid.B/2024/PN Kln, assessing the element of intent based on the testimony of forensic experts from the perspective of criminal law theory. This normative legal research uses a statutory and case-based approach. Data collection through literature studies includes regulations, court decisions, and legal literature, analyzed qualitatively. As a result, the panel of judges declared that all elements of Article 338 of the Criminal Code-whosoever, takes the life of another person, and intentionally-were fulfilled based on the testimony of witnesses, the defendant, and the Visum et Repertum. The element of intent was supported by the testimony of forensic experts regarding the cause of death, related to the theory of will (wilstheorie) and knowledge (voorstellingstheorie). The testimony of forensic experts plays a crucial role in strengthening the evidence of intent in murder.